2011
DOI: 10.1021/jo101865y
|View full text |Cite
|
Sign up to set email alerts
|

Thionations Using a P4S10−Pyridine Complex in Solvents Such as Acetonitrile and Dimethyl Sulfone

Abstract: Tetraphosphorus decasulfide (P(4)S(10)) in pyridine has been used as a thionating agent for a long period of time. The moisture-sensitive reagent has now been isolated in crystalline form, and the detailed structure has been determined by X-ray crystallography. The thionating power of this storable reagent has been studied and transferred to solvents such as acetonitrile in which it has proven to be synthetically useful and exceptionally selective. Its properties have been compared with the so-called Lawesson … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
60
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(61 citation statements)
references
References 100 publications
1
60
0
Order By: Relevance
“…26 Initial attempts to form the thiosquaramide derivatives 5–8 using Lawesson's reagent proved unsuccessful, while reaction with tetraphosphorus decasulfide (P 4 S 10 ) gave thiosquaramide products in low yield as part of a complex mixture of products. However we found that the zwitterionic P 4 S 10 ·pyridine complex, formed by reaction of P 4 S 10 in refluxing pyridine, 27 allowed the conversion of oxosquaramides 1–4 into thiosquaramides 5–8 in 66%, 48%, 37% and 60% yields respectively (Scheme 1). This strategy afforded each of the thiosquaramides in reasonable yields and 6–8 were easily purified by flash chromatography, while thiosquaramide 5 needed no further purification.…”
Section: Resultsmentioning
confidence: 98%
“…26 Initial attempts to form the thiosquaramide derivatives 5–8 using Lawesson's reagent proved unsuccessful, while reaction with tetraphosphorus decasulfide (P 4 S 10 ) gave thiosquaramide products in low yield as part of a complex mixture of products. However we found that the zwitterionic P 4 S 10 ·pyridine complex, formed by reaction of P 4 S 10 in refluxing pyridine, 27 allowed the conversion of oxosquaramides 1–4 into thiosquaramides 5–8 in 66%, 48%, 37% and 60% yields respectively (Scheme 1). This strategy afforded each of the thiosquaramides in reasonable yields and 6–8 were easily purified by flash chromatography, while thiosquaramide 5 needed no further purification.…”
Section: Resultsmentioning
confidence: 98%
“…The classical method for the thionation of carbonyl compounds is sulfuration by using Lawesson′s reagent, which has been summarized in several comprehensive reviews 74. Other sulfuration agents with similar S‐transfer mechanisms for the thionation of carbonyl compounds, such as Belleau′s reagent, Davy′s reagent, P 4 S 10 , etc.,75 are summarized in Scheme .…”
Section: Cs Bond Construction By Different Sulfuration Agentsmentioning
confidence: 99%
“…The py 2 P 2 S 7 was synthesized by refluxing stoichiometric amounts of P 4 S 10 and elemental sulfur in pyridine. Two years later the swedish group of Prof. Bergman also published the crystal structure of py 2 P 2 S 5 and discussed its use as thionating agent 8…”
Section: Introductionmentioning
confidence: 74%